Program Pendidikan Vokasional untuk Penerapan Teknologi Tepat Guna dalam Agribisnis - Alif Ilham Akbar Fatriansyah; Astri Shabrina; Muhammad Syarifudin (Institut Agama Islam Ma’arif NU (IAIMNU) Metro Lampung, 2021)
Limited access to technology and information among farmers in rural areas is one of the obstacles to developing productive and sustainable agribusiness. This community service program aims to increase farmer capacity through vocational education focused on the application of Appropriate Technology in agribusiness activities. The program was conducted in the Lampung region, with the primary participants being corn and horticulture farmers. Implementation methods included counseling, hands-on practice, and intensive mentoring for five types of Appropriate Technology: drip irrigation systems, and manual row planting tools. Evaluation results showed a significant increase in participants' understanding and skills in using Appropriate Technology, as well as the growth of local initiatives for independent tool replication and development. The program also demonstrated that Appropriate Technology -based vocational education is not only effective in increasing production efficiency but also fosters attitudinal change toward adaptive and innovative agribusiness. This program is recommended for replication in other rural areas with cross-sectoral support to achieve technology-based farmer independence.